The Influence of Short‑Term Hipocaloric Nutrition on Bodyweight Reduction in Lithuanian Olympic Team Wrestlers (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. These days many athletes of combat sports prior contest practice unsafe hipocaloric diets. Hypothetically the content of macronutrient and micronutrient composition of wrestlers’ food rations must be corrected individually during the time of bodyweight loss and after weigh control.Research aim of the present study was to examine the effects of bodyweight reduction on athletes’ body weight (BW), lean body mass (LBM), body fat (BF), body fluid (BFL), body protein (BP) and minerals. Research methods. Wrestlers (n = 10) were measured before, at the end (before weight control) rapid bodyweight reduction and 2 days after contest. Food records were analyzed and macronutrient and micronutrient contributions from meals were assessed. The measures of body mass components were taken using BIA tetra-polar electrodes.Research results. Analysis of wrestlers 4-day food records revealed average values at 18.2 ± 10.6 kcal·kg -1 ·day -1 , 0.8 ± 0.4 g·kg -1 ·day -1  of proteins, 2.0 ± 1.5 g·kg -1 ·day -1   of carbohydrates and 0.8 ± 0.4 g·kg -1 ·day -1  of fat throughout the period of rapid bodyweight reduction. Low total energy intake contributed to the insufficient on take of vitamins A, B 1 , B 2 , PP, D, E, B 6 , folic acid and minerals as potassium, calcium, phosphorus, magnesium, iron, zinc intakes during the rapid bodyweight loss season. Additionally wrestlers followed low-carbohydrate and high-fat diet and did not consume adequate energy or carbohydrate diet after the contest.Discussion and conclusions. During rapid bodyweight loss period athletes showed a significant decrease in BM (–3.7 ± 1.9 kg, p < 0.05), LBM (–1.5 ± 1.3 kg, p < 0.05), BF (–2.1 ± 0.6 kg, p < 0.001), BFL (–1.1 ± 0.9 kg, p < 0.05), minerals (–0.2 ± 0.1 kg, p < 0.05), but not BP (–0.2 ± 0.1 kg, p  ≤ 0.05). After contest wrestlers had significant increases in BM (+3.1  ± 1.9 kg, p < 0.05), BF (+2.6 ± 0.5 kg, p < 0.001) and minerals (+0.2 ± 0.1 kg, p < 0.05), but non-significant increase in LBM (+1.0  ± 1.8 kg, p > 0.05) and BFL (+0.7 ± 1.3 kg, p < 0.05). Wrestlers’ food rations must be corrected individually during the time of bodyweight loss, after weigh control and follow-up recovery, during the period of contest.Keywords: nutrition, wrestlers’ food rations, weight reduction.